Can the spinodal decompositon generate a resistivity anomaly in a binary alloy? - Luiggi, Ney; Chávez, Emily (Ciencia)
In this work we discuss the real dependance that the residual electric resistivity has on the aging time, when the spinodal mechanism is responsible for the decomposition of a binary alloy. We use the isotropic aproximation for the resistivity and linear, as well as nonlinear theory of spinodal decomposition. Our results, in both cases, show an increment in the resistivity up to a point which is determined, in the nonlinear theory, by the critical amplitude of fluctuation of concentration, which disagees with other results reported in the literature. With these results we show that this mechanism by itself cannot explain the anomaly exhibited electrical resistivity.